Student Verbal Impoliteness in Discussion-Based Mathematics Classrooms: A Qualitative Study on Interaction and Participation - Maria Carmelita Tali Wangge; Maria Fatima Wio; Angela Merici Bhebhe (Journal of Transdisiplinary Studies in Education, 2025)
Background: Discussion-based mathematics instruction is intended to promote shared reasoning and active participation, yet its effectiveness depends on the quality of students’ verbal interaction. When communication shifts toward interruption, dismissive remarks, or inappropriate tone, the collaborative nature of discussion may be weakened. Aims: This study explores how verbal impoliteness is enacted by students during discussion-based mathematics learning and investigates its influence on classroom interaction and participation. Methods: A descriptive qualitative approach was applied in an eighth-grade mathematics classroom implementing group discussions. Data were generated through direct classroom observations, semi-structured interviews with selected students and the teacher, and supporting documentation such as field notes. The data were examined through thematic analysis to identify recurring patterns of impolite verbal behavior and their effects on interaction. Result: The study found that verbal impoliteness commonly appeared in the form of unsolicited interruptions, sarcastic or demeaning comments, and raised intonation when responding to peers. These behaviors disrupted the continuity of discussion, discouraged some students from contributing, and led to unequal participation within groups. As a result, interaction became dominated by a limited number of voices, while others withdrew from the exchange of ideas during mathematical problem solving. Conclusion: Verbal impoliteness significantly shapes the quality of interaction and participation in discussion-based mathematics classrooms. Establishing shared norms of respectful dialogue and consistently guiding students toward constructive communication are essential for sustaining inclusive and meaningful mathematical discussion.